SIFAT FISIKA PAPAN SEMEN DARI CAMPURAN LIMBAH BATANG SAWIT - Nadapdap, Rosmaina Julianti; Rahayu, Yuyu; Husodo, Susilo Budi (Jurnal Teknologi Terapan, 2025)
This study investigates the physical properties of cement boards made from oil palm trunk waste and evaluates the effect of varying cement-to-palm trunk waste ratios (70:30, 75:25 and 80:20). The independent variable is the cement-to-waste ratio, and the dependent variables include density, moisture content, thickness swelling, and water absorption. Results show that the density of the boards ranges from 0.70 g/cm³ to 1.02 g/cm³, moisture content from 6.79% to 14.49%, thickness swelling after 24 hours of immersion from 17.50% to 70.00%, and water absorption from 40.41% to 68.04%. Ratio 70:30 and 75:25 meet Indonesian National Standard (SNI) criteria for density and moisture content, but thickness swelling exceeds the standard, indicating poor dimensional stability. Increasing cement content improves density and reduces moisture content, but challenges remain in achieving dimensional stability and water resistance. These findings suggest that while oil palm trunk waste can be used in cement board production, further optimization, such as additive incorporation or feedstock modification, is needed to enhance water resistance and stability.